Dimercaptosuccinic acid scintigraphy vs. ultrasound for renal parenchymal defects in children - Marceau-Grimard, Maryse; Marion, Audrey; Côté, Christian; Bolduc, Stephane; Dumont, Marcel; Moore, Katherine (Canadian Urological Association Journal, 2017)
Introduction: Dimercaptosuccinic acid (DMSA) scintigraphy is the gold standard in the evaluation of renal parenchymal defects and is widely used in the pediatric population. As more recent ultrasound equipment was purchased at our tertiary pediatric centre, our objective was to evaluate if renal ultrasound (US) results are equivalent or sufficient when compared to DMSA scintigraphy in the assessment of renal anomalies. Methods: The charts of all 463 patients who underwent DMSA scintigraphy between January 2009 and May 2014 at our pediatric tertiary centre were reviewed. The objective was to look for correlation between US and DMSA scan results for renal scars/dysplasia. A hundred and sixty pediatric patients followed with US and DMSA scan for a total of 285 renal units remained for evaluation after exclusions. Timing of the exams, urinary tract infection (UTI), and indication for imaging were reviewed. Results with older (105 patients) and newer (55 patients) US equipment were compared. Results: Among the 285 renal units evaluated, 39 (14%) had renal parenchymal defects shown by US and 87 (31%) by DMSA scintigraphy (sensitivity 36%, specificity 96%). The DMSA scan was normal for eight abnormal kidneys (3%) on US. The results were not statistically significant when compared to exams performed with newer or older US machines. Conclusions: At our institution, US data are not sensitive enough to give reliable information about renal parenchymal defects, even with newer equipment. DMSA scintigraphy still remains mandatory for the evaluation of renal anomalies, but could be optional if the US exam indicates parenchymal defects.